Has laparoscopic surgery reduced negative appendectomy rates? - Dincer, Mürşit; Lıman, Rumeysa Kevser (My University, 2020)
Introduction: Negative appendectomies can still be performed despite improvements in imaging methods. As a result of advances in minimally invasive surgery, laparoscopic appendectomy rates have increased in the treatment of acute appendicitis. The aim of this study was to investigate the effect of laparoscopic surgery on negative appendectomy rates. Materials and Methods: Patients who underwent appendectomy for acute appendicitis between December 2016 and December 2018 were retrospectively reviewed. A total of 293 patients were involved in the study. The patients were divided into two groups: open appendectomy and laparoscopic appendectomy. The demographic characteristics and histopathological diagnosis of the patients were recorded. Differences in patients with histopathological diagnoses, except for acute appendicitis, were analyzed. Results: There were 119 cases in the laparoscopic appendectomy group and 174 cases in the open appendectomy group. The mean age was 35.82 (± 16.48) years. One hundred seventy-six of the cases were male and 117 were female. There was no statistically significant difference between the two groups in terms of demographic characteristics. The same number of negative appendectomy cases was found in both groups. The result was also statistically insignificant. Conclusion: This study showed that laparoscopic appendectomy did not reduce the negative appendectomy rates. Despite the advances in imaging methods, such as ultrasound and computed tomography, and the advantages of laparoscopy in abdominal exploration, the rates of negative appendectomy are still considerable. Despite all technological developments, anamnesis and physical examination remain important in the diagnosis of acute appendicitis.
Keywords: Cerrahi